Galvanic plating for 3D-MID applications - Kordaß, Timo; Franke, Jörg (Proceedings of the 2014 37th International Spring Seminar on Electronics Technology, ISSE 2014, 2014)
This paper gives an overview about the advantage of galvanic plating for 3D-MIDs. At first it is explained how the laser direct structuring process is proceeded. Exemplary on a serial application for motorcycles it shows the challenges for the chemical standard plating in the serial processes in the first part. The second part illustrates the differences in the plating processes between the galvanic and the chemical precipitation. The advantages with major coating thickness for further developed applications are mentioned. It is also given the particular specifics need to be considered in the development for the galvanic process.
CRIS-Team Scopus Importer:2023-03-07

Laser-assisted Selective Activation of Injection Molded Chip Packaging Devices with Thermoset Substrate Materials for Intelligent Connectivity Systems in Automobiles - Kordaß, Timo; Bachy, Bassim; Weisser, Mathias; Franke, Jörg (Procedia CIRP, 2017)
The development of sensors, such as in the automotive sector is characterized by increasing miniaturization and variety. Higher integration of functions in electrical and mechanical applications is therefore a logical consequence for further development. In this connection especially technologies can persuade, enabling high design flexibility, combination of electrical and mechanical functions and embedding of further applications. Mechatronic integrated devices are a considerable solution combining mechanical and various electrical functions in an entire component together. Specifically, the ability for insert moulding of MEMS sensor chips and the ability to create circuit carrier in nearly any shape with selective traces and laser drilled vias suite for this production method. A particular focus is on the durability of very fine conductor tracks. With increasing miniaturization especially in high temperature and high voltage applications the typical thermoplastic based substrate materials with their thin chemical plated circuits, reach boundaries in the thermal and mechanical properties. The use of thermoset materials provides a new suitable alternative in this field. The cross-linked, molecular structured thermosets obtain high temperature resistance, combined with high dimensional stability. The thermal expansion is comparative low. With appropriate selection of compound fillers, aligned laser activation parameters and suitable circuit plating system a reliable CTE composition of all materials can be achieved. Thermosetting plastic compounds with laser-activatable additives are indeed in focus of current researches. However, laser-based method for the selective activation of thermosets is currently not available on the market. As a result, it is investigated into alternative laser assisted activation methods which do not require special additives in the substrate compound for electro chemical potential. Instead an assimilated chemical palladium activation is utilized subsequently. Of particular importance is distinct and selective activation with suitable laser parameters, as well as the following electroless chemical copper and additionally galvanic copper plating with appropriate surface quality for electronic surface mount and assembly technologies. Within the article, the research results will be presented, describing the method and giving an insight into the qualified process parameters for the laser and palladium activation, their correlations among themselves as well as the implications onto the following chemical and galvanic plating.
CRIS-Team Scopus Importer:2023-03-07
Keywords: 3D-MID; chemical plating; electronic manufacturing; selective ionogenic and colloidal palladium activation; thermoset substrates

Simulation and experimental investigation for the 2D and 3D laser direct structuring process - Bachy, Bassim; Süß-Wolf, Robert; Kordaß, Timo; Franke, Jörg (International Journal of Advanced Manufacturing Technology, 2017)
The molded interconnected devices (MID) technology is vastly growing as an important innovative technology in the field of electronics production. The laser direct structuring (LDS) method is one of the most common available technologies for building up MID’s products. The current existing knowledge in industry and in research about the standards in the respective manufacturing processes and process parameters is up to now not fully comprehensive in terms of mutual influencing and dependencies on each other. This is particularly the case for the three-dimensional applications and micro products. In the present contribution, a new simulation procedures based on a three-dimensional finite element model (FEM) has been developed. The effect of each of latent heat of fusion and temperature on the material properties as well as the 3D Gaussian heat source for the laser beam has been considered in this work. The used material was a polymer plate poly ether ether ketone (PEEK). The effect of the process parameters including laser power, speed, frequency, hatching percent or overlap between the laser lines, the laser incident angle, and the focal length have been investigated in experiments and simulations. The present simulation can be used to predict, temperature distribution, maximum temperature, groove dimensions, and groove profile at different process parameters setup. The theoretical and the experimental results can show a good accordance. It can be concluded that the FEM simulation can be used efficiently for predicating, analyzing, and optimizing the 2D/3D laser parameters for the LDS process.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Finite element model; Laser direct structuring process; Laser process simulation; Molded interconnect devices